Profile of Learning Environmental Literacy in Elementary School - Nugraha, Lukman; Saud, Udin Syaefudin; Hartati, Tatat; Damaianti, Vismaia S. (PrimaryEdu : Journal of Primary Education, 2022)
Environmental literacy play a crucial role in instilling awareness in children about the importance of protecting the environment. The aim of this study was to describe the learning profile that has an impact on environmental literacy of elementary school students. This research used descriptive qualitative research. The sources of data in this study are 4 elementary schools in Subang Regency from 4 different sub-districts. The data collected was data regarding the profile of students' environmental literacy learning in the Elementary School by focusing on the profile of environmental knowledge, attitudes, and environmental behavior based on environmental literacy measurements. Data collection techniques were carried out by triangulation (combined) through interview and survey techniques. The instruments used in this research were interview guidelines and questionnaires/questionnaires. The data analysis technique was carried out through the stages of data reduction, data presentation, and drawing conclusions. This research showed that: 1) Environmental knowledge profiles in school local content have been well applied in the curriculum which can be seen in the conditioning of the learning environment that blends with nature, and 2) The profile of environmental attitudes and behavior in learning has been well integrated at every grade level, as evidenced by the collaboration between students in protecting the environment. This study recommends educators to focus on environmental literacy to renew their understanding of the importance of protecting the environment and forming social awareness of the surrounding environment. A suggestion for further research is to investigate this trend among public or private schools in several regions of Indonesia.